Naše izkušnje z uporabo balonske kifoplastike pri poškodbah hrbtenice - Brilej, Drago (Zdravniški vestnik, 2008)
Background Many investigators concluded that the burden of vertebral spine fracture can be substantial in chronic pain, a marked reduction in health-related quality of life and high healthcare costs. Minimally invasive surgical techniques of bone cement injection into fractured vertebrae such as balloon kyphoplasty stabilize the fracture and partly restore vertebral heightreducing kyphotic deformity. Balloon kyphoplasty has been favoured by a large number of patients because they experience significant short-term pain relief and improvement in function.Methods In Department of Traumatology, Celje General Hospital, in 2004 we started to treat selected fractured vertebrae by standalone balloon kyphoplasty and cement augmentation. In the pilot study the effectiveness and safety of Balloon Kyphoplasty as a new method of treatment of traumatic compression fractures of the thoracolumbar spine in patients older than 40 years was assessed. We consecutively analysed nine patients (6 male and 3 female patients). The average age was 59 years (42-75). In 4 cases the fractured vertebra was L1, in 3 cases L2 and one case L4 and one Th12. According to the Magerl classification five of them were A1, two A2, and two of them were A3 burst fractures. Safety of the method was assessed and also the x-ray (vertebral body height, Cobb angle) and clinical efficacy of the method (pain measured by visual analogue pain scale, mobility measured by Oswestry low back pain questionary, quality of life measured by SF12). Results No severe or clinically relevant complications were observed. The method demonstrated restoration of the vertebral bodyćs shape (from 42 % to 89 % of predicted vertebral mid body height; from 16 to 10° kyphotic angulations). We recorded a significant decrease in pain score (89 % without or minimal pain), and improved quality of life after procedure (no severe disability, SF 12 score 81 %). (Abstract truncated at 2000 characters)
Keywords: Kifoza; kirurško zdravljenje; Kyphosis; Osteoporosis; Osteoporoza; Spinal Fractures; Spinalni zlomi; Surgery; Treatment Outcome; vretenca; Zdravljenje, izid; zlomi